Insulin Requirements and Carbohydrate to Insulin Ratio in Normal Weight, Overweight, and Obese Women With Type 1 Diabetes Under Pump Treatment During Pregnancy: A Lesson From Old Technologies - Festa, Camilla; Fresa, Raffaella; Visalli, Natalia; Bitterman, Olimpia; Giuliani, Chiara; Suraci, Concetta; Bongiovanni, Marzia; Napoli, Angela (Frontiers in Endocrinology, 2021)
Aim:The primary aim of this study was to assess insulin requirements and CHO/IR in normal weight, overweight and obese pregnant women with type 1 diabetes across early, middle, and late pregnancy. Methods:In this multicenter, retrospective, observational study we evaluated 86 of 101 pregnant Caucasian women with type 1 diabetes under pump treatment. The women were trained to calculate CHO/IR daily by dividing CHO grams of every single meal by insulin units injected. Since the purpose of the study was to identify the CHO/IR able to reach the glycemic target, we only selected the CHO/IR obtained when glycemic values were at target. Statistics:SPSS20. Results:We studied 45 normal weight, 31 overweight, and 10 obese women. Insulin requirements increased throughout pregnancy (p<0.0001 and <0.001 respectively) in the normal and overweight women, while it remained unchanged in the obese women. Insulin requirements were different between groups when expressed as an absolute value, but not when adjusted for body weight. Breakfast CHO/IR decreased throughout pregnancy in the normal weight women, from 13.3 (9.8-6.7) at the first stage of pregnancy to 6.2 (3.8-8.6) (p=0.01) at end stage, and in the overweight women from 8.5 (7.1-12.6) to 5.2 (4.0-8.1)(p=0.001), while in the obese women it remained stable, moving from 6.0 (5.0-7.9) to 5.1 (4.1-7.4)(p=0.7).Likewise, lunch and dinner CHO/IR decreased in the normal weight and overweight women (p<0.03) and not in the obese women. The obese women gained less weight than the others, especially in early pregnancy when they even lost a median of 1.25 (–3.1 –1.1)kg (p=0.005). In early pregnancy, we found a correlation between pregestational BMI and insulin requirements (IU/day) or CHO/IR at each meal (p<0.001 and p=0,001, respectively). In late pregnancy, a relationship between pre-gestational BMI and CHO/IR change was found (P=0.004), as well as between weight gain and CHO/IR change (p=0.02). The significance was lost when both variables were included in the multiple regression analysis. No differences in pregnancy outcomes except for a higher pre-term delivery rate in the obese women. Conclusion:Pre-gestational BMI and weight gain may play a role in determining CHO/IR during pregnancy in women with type 1 diabetes under pump treatment.